KOHESI DAN KOHERENSI TEKS PIDATO â€œAPEC CEO SUMMIT 2014â€ OLEH JOKO WIDODO - ANAHAMU, MARYATI LIKA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT Â  This skripsi is made as a requirement to obtain bachelor Degree in English in Sam Ratulangi University. This research entitled â€œThe Cohesion and Coherence of Speech at â€œAPEC CEO SUMMIT 2014â€ by Joko Widodo. It is attempt to analyze and explain the cohesion and coherence items in Joko Widodo speech. There are three steps to finish this research. First step is preparation, the writer finds the speech of Joko Widodo, she also reads some books about language, linguistics, discourse analysis, relevant theories, andÂ  articles from internet which relevant to the topic of this study. Second step is data collection, the writer downloads the speech of Joko Widodo â€œAPEC CEO SUMMIT 2014â€ from www.englishindo.com, reads the speech for several times to have deeper understanding and identifies the items according to theory of Juez Â (2009). Third step is data analysis. The method used in this research is taken from Alba-Juez (2009) and supported by the theory of Halliday & Hassan (1976) and Aarts and Aarts ((1982). The theory consists of Cohesion: pronoun, substitution, ellipsis, conjunction, lexical, and Coherence: marked coherence and unmarked coherence. The result of this research shows that in cohesion there are 112 pronouns, 6 substitutions, 1 ellipsis, 6 conjunctions, 14 lexical cohesions. In this speech, there are 22 marked coherence and there is no unmarked coherence. Keywords: discourse analysis, speech, cohesion and coherence, Joko Widodo